Artificial Life and Intelligent Agents First International Symposium, ALIA 2014, Bangor, UK, November 5-6, 2014. Revised Selected Papers - Headleand, Christopher J.; Teahan, William J.; Ap Cenydd, Llyr (Communications in Computer and Information Science,, 2015)
This book constitutes the refereed proceedings of the First International Symposium on Artificial Life and Intelligent Agents, ALIA 2014, held in Bangor, UK, in November 2014. The 10 revised full papers were carefully reviewed and selected from 20 submissions. The papers are organized in topical sections on learning and evolution; human interaction; robotic simulation.